Pesquisa de salmonella em mutuns (mitu mitu) mantidos em cativeiro - Vaz, Andréia Nakashima; Armando, Alexandre Paulo; Ribeiro, Andréa Rentz; Zancan, Fábio Tavares [UNESP]; Brisola, Marcelo Landim (Universidade Federal de Goiás, 2015)
We collected 50 samples of curasow feces from the Scientific and Cultural Breeding Center in the city of Poços de Caldas. The samples were enriched in broth medium Tetrationato and Cystine-selenite and plated on Salmonella Shigella (SS), Mac Conkey (MC), endo-C (EC), Brilliant Green (VB) and Eosyn Methilen Blue EMB, remaining at 37 °C for 24h. Colonies suspected of Salmonella were inoculated in tubes containing Agar Triple Sugar Iron (TSI) and again incubated at 37 ºC for 24h. Tubes with characteristic growth were submitted to slide agglutination test with polyvalent somatic and flagellar serum. The medium SS, MC and VB were the most efficient for growing, and 36% of samples were positive for Salmonella spp. As birds are important reservoirs of Salmonella spp and it may represent a high risk to human health, there is a need to implement a cleaning routine in enclosures avoiding contamination between the enclosures and the consequent entrainment of these micro-organisms, by the keepers until their homes or other venues. The presence of Salmonella in breeding centers may be responsible for lower hatchability of eggs, undermining the purpose of the entity, which is to study and maintain the various birds species.

Foram colhidas 50 amostras de fezes de mutuns do Criadouro Científico e Cultural Poços de Caldas. A amostras foram enriquecidas em meio caldo Tetrationato e Selenito-Cistina e plaqueadas em Salmonella Shigella (SS), Mac Conkey (MC), Endo-C (EC), Verde Brilhante (VB) e Eosina Azul de Metileno (EMB), a 37º C por 24h. Colônias suspeitas de Salmonella spp foram inoculadas em tubos contendo Ágar Tríplice Açúcar Ferro (TSI) e incubadas a 37 ºC por 24 h. Os tubos com crescimento característico foram submetidas ao teste de aglutinação em lâmina com soros polivalentes somático e flagelar. Os meios SS, MC e VB foram os mais eficientes para o cultivo, sendo 6% das amostras, positivas para Salmonella spp. Sabendo-se que as aves são reservatórios importantes de spp e que esta pode representar um alto risco para a saúde humana, há a necessidade de implantação de uma rotina de limpeza dos recintos para evitar contaminação entre os recintos e o consequente carreamento destes micro-organismos, pelos tratadores, até suas residências ou outros recintos. A presença da Salmonella spp em criadouros pode ser responsável pela menor eclodibilidade dos ovos, prejudicando o objetivo da entidade, que visa o estudo e a manutenção das diferentes espécies de aves silvestres.
Survey of salmonella in curassows breeding center of wild animals
Keywords: Curassows; Feces; Microbiological culture; Salmonella; Cultura microbiológica; Fezes; Mutum; Salmonella